Mean Platelet Volume and Vitamin D Level - Cumhur Cure, Medine (The Korean Society for Laboratory Medicine, 2014)
BACKGROUND: Vitamin D deficiency and a high mean platelet volume (MPV) are related to cardiovascular disease. We investigated whether vitamin D deficiency is associated with high MPV. METHODS: This study included 434 patients without chronic disease who were not taking vitamin D or calcium supplements. Vitamin D was measured by chemiluminescent microparticle immunoassay on the Architect-I2000 system (Abbott Diagnostics, USA), and MPV was measured on the Cell-Dyn Ruby analyzer (Abbott Diagnostics). Patients were divided into Groups 1 (138 [men/women, 46/92]), 2 (148 [men/women, 54/94]), and 3 (148 [men/women, 50/98]) according to vitamin D levels of <10 ng/mL, 10-20 ng/mL, and >20 ng/mL, respectively. RESULTS: The vitamin D level in Group 1 (7.7±1.9 ng/mL) was lower than that in Group 2 (15.1±1.6 ng/mL, P<0.001) and Group 3 (25.6±6.3 ng/mL, P<0.001). The MPV in Group 3 (7.5±1.0 fL) was lower than that in Group 1 (8.1±1.1 fL, P<0.001) and Group 2 (7.9±1.0 fL, P=0.009). Linear regression analysis showed that low levels of vitamin D (β=-0.109, P=0.019) was independently associated with increased MPV. CONCLUSIONS: There was a strong association between a low vitamin D level and a high MPV; therefore, vitamin D deficiency may be associated with increased MPV.